The Use of The Make a Match Model in Arabic Language Learning to Improve Arabic Vocabulary Mastery of Grade VII Students at MTs Wanasari - Daffa Aria Ghaisan; Isop Syafe'i; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to evaluate the effectiveness of using the Make a Match learning model in improving the Arabic vocabulary mastery of class VII students at MTs Wanasari. The Make a Match method is a cooperative learning strategy that involves students in looking for matching pairs of cards between questions and answers, which is designed to increase student interaction and active participation. This research uses a quasi-experimental method with a pretest-posttest design. The research subjects were class VII students who were chosen randomly. Data was collected through Arabic vocabulary tests before and after implementing the Make a Match model. The research results showed that there was a significant increase in students' mastery of Arabic vocabulary after implementing this learning model. Students become more motivated and active in the learning process, which has a positive impact on improving their learning outcomes. These findings indicate that the Make a Match model is effective in improving Arabic vocabulary mastery and can be recommended as an innovative learning strategy at MTs Wanasari.